ANALISIS NILAI TAMBAH DAN EFISIENSI PRODUKSI CETAK OFFSET PADA INDUSTRI PERCETAKAN DI KOTA PALEMBANG - Anton Trianto (Department of Development Economics, Universitas Sriwijaya, 2004)
This research is intended to analyze the level of value added and efficiency of offset printing production at small printing qffice industry in Palembang. Some theories applied on this research namely production and production cost, value added and efficiency. Beside that, sereral comparisons are added to compare the results of this research with others that have been ohsen-ed previously. The results indicate that the average level of value added and efficiency of offset prim in production are Rp. 3.279.200 and 0,56 per month. Compare with the results which are achien!d by other industries, the levels are still in low stage relatively. It means that, in offset printing production process, the expenditure proportion of intermediate cost is still hi her than the proceeds proportion of output value and value added. Key word: value added, eficiency, offset printing production